METODE 2M2PR BERBASIS QUANTUM LEARNING DAN PERMAINAN TRADISIONAL DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Praheto, Biya Ebi; Sayekti, Octavian Muning (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
This article aims to describe how the application of the 2M2PR (Motivation, Multimedia, Game, Strengthening, Celebration) Method Based on Quantum Learning and Traditional Games in Indonesian language learning in elementary schools. This research is included in library research. The result obtained is that the integration of traditional games is an innovative effort in the language learning process related to national culture. Many methods can be developed in learning such as the 2M2PR method based on quantum learning and traditional games. Traditional games can be integrated with language learning such as snake and ladder games and crank games and many more. In this case, the teacher must have a creative attitude in selecting and modifying traditional games so that they are following the material to be taught. It is hoped that the 2M2PR method and the integration of traditional games in Indonesian language learning can increase attractiveness in language learning and make it easier for students to convey and understand the subject matter. In addition, integrating traditional games, can foster a sense of love for culture and introduce national culture to students from an early age.Ã‚Â Ã‚Â